A Noteon Terms of Trade Shocks and the Wage Gap. (IMF Working Papers; Working Paper ;, 2010)
Using Chilean data, we document that for resource-rich small open economies the effects of terms of trade shocks on the wage gap (between skilled and unskilled workers) depend on factor intensities in the non-tradable sector, following the model in Galiani, Heymann, and Magud (2010). For a skilled-intensive non-tradable sector we show that improvements in the terms of trade benefit skilled workers. We also show that this relation holds at the industry level: the wage gap widens in skilled-intensive sectors while it shrinks in unskilled-intensive ones, the more so as terms of trade volatility decreases.